Breakdown characteristics of glass fibre reinforced plastic for termination of high temperature superconducting cable - Dung, Nguyen Van; Truong, Le Vinh (Vietnam Journal of Science and Technology, 2022)
A study on the effect of the physical states of nitrogen on breakdown properties of glass fibre reinforced plastic was carried on. Surface breakdown and volume breakdown of glass fiber reinforced plastic in nitrogen gas, cryogenic nitrogen gas and liquid nitrogen under AC voltages were investigated. In addition, breakdown strength-time to breakdown characteristics of glass fiber reinforced plastic in these insulating media was also examined. The experimental data showed that surface breakdown strength and volume breakdown strength of glass fiber reinforced plastic were significantly dependent on surrounding media, and similar results were obtained with breakdown strength-time to breakdown experiments.